2021
DOI: 10.1002/ange.202013791
|View full text |Cite
|
Sign up to set email alerts
|

Ferric Heme Superoxide Reductive Transformations to Ferric Heme (Hydro)Peroxide Species: Spectroscopic Characterization and Thermodynamic Implications for H‐Atom Transfer (HAT)

Abstract: A new end‐on low‐spin ferric heme peroxide, [(PIm)FeIII−(O22−)]− (PIm‐P), and subsequently formed hydroperoxide species, [(PIm)FeIII−(OOH)] (PIm‐HP) are generated utilizing the iron‐porphyrinate PIm with its tethered axial base imidazolyl group. Measured thermodynamic parameters, the ferric heme superoxide [(PIm)FeIII−(O2⋅−)] (PIm‐S) reduction potential (E°′) and the PIm‐HP pKa value, lead to the finding of the OO−H bond‐dissociation free energy (BDFE) of PIm‐HP as 69.5 kcal mol−1 using a thermodynamic square … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…As the temperature was increased from 323 to 353 K, the value of peroxide decreased significantly. The results showed that the peroxide decomposition rate was faster than that of peroxide because of the instability of O–O bonds [ 39 ]. Many free radicals were released to activate levopimaric acid oxidation at depth with oxygen [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…As the temperature was increased from 323 to 353 K, the value of peroxide decreased significantly. The results showed that the peroxide decomposition rate was faster than that of peroxide because of the instability of O–O bonds [ 39 ]. Many free radicals were released to activate levopimaric acid oxidation at depth with oxygen [ 40 ].…”
Section: Resultsmentioning
confidence: 99%